KORELASI pH DENGAN KADAR LDH PADA TROMBOSIT KONSENTRAT DALAM BERBAGAI WAKTU PENGOLAHAN SELAMA MASA PENYIMPANAN - , MUTIARA AIDHA BETAVIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
BACKGROUND : Quality control of thrombocyte concentrate is performed in purpose to know the profile of Platelet Storage Lession (PSL) during the storage. One of the PSLâs parameters are pH and LDH level. Both are directly involved in metabolisme of thrombocyte to produce energy. The significance declined of pH value and the significance increased of LDH level can effect the quality of thrombocyte concentrates. OBJECTIVES : To know the correlation between pH value and LDH level on thrombocyte concentrates during the storage that processed on 0 hours, 6 hours, and 16 hours. METHODS : This research used observational method with cross-sectional research design which was performed in RSUP Dr Sardjito. The research samples were 15 of thrombocyte concentrate bags. Then, sample divided into 3 categories (group 1 which is processed on 0 hour, group 2 which is processed on 6 hours, and group 3 which is processed on 16 hours), and the value of pH and level of LDH were measured using Blood Gas Analyzer and Chemistry Analyzer respectively during storage on day 0, day 1, day 3, and day 6. The result were analyzed using Pearson Correlation Method. RESULTS: The results showed a significant correlation between pH value and LDH level on thrombocyte concentrate of group 1 (r:-0,52